ANALISIS PENGARUH CUSTOMER RELATIONSHIP MANAGEMEN (CRM) TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN PADA PT JASA RAHARJA (PERSERO) CABANG RIAU DI KOTA PEKANBARU - Firles, Masna; Zulkarnain, Zulkarnain; Alwie, Alvi Furwanti (Jurnal Tepak Manajemen Bisnis, 2018)
Jasa Raharja (Persero) is a state-owned company that is mandated toprovide traffic accident accidents and public passengers in Indonesia. Thisprivilege will not last long, given the monopoly rights in a number of governmentownedcompanies have the potential to be abolished. Therefore, the companyneeds to do a study on how strong the relationship that Jasa Raharja has with itsbusiness customers. The research was conducted at Jasa Raharja (Persero)Branch of Riau. The purpose of this research is to know the direct and indirecteffect of CRM with variable of Human Resources, Process and Technology toCustomer Satisfaction and Customer Loyalty. This research population isbusiness consumer Jasa Raharja that is the owner of public land passengertransportation which is domiciled in Pekanbaru city. The sample was determinedby Proportionate Random Sampling of 173 respondents. Analytical tool used isdescriptive analysis and Structural Equation Modeling (SEM). The results showedthat human resources, processes and technology have a positive and significanteffect on customer satisfaction and customer loyalty. It is recommended toimprove human resource communication skill, create customer-focused vision andmission and create accurate and up-to-date database in order to increasecustomer satisfaction which leads to customer loyalty of Jasa Raharja.